Multiple genomic features filtration to improve protein-protein interactions prediction [electronic resource] - Rosfuzah Roslan, 1984-; Fakulti Sains Komputer dan Sistem Maklumat (2010)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2010